Efektivitas Larvasida Ekstrak Kulit Pisang Raja (Musa paradisiaca var. Raja) Terhadap Larva Aedes sp. Instar III - Jamal, Siti Arnis Nurhidayah; Susilawaty, Andi; Azriful, Azriful (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Various ways could be implemented to prevent or minimize the dengue fever’s transmission, one of which is the vector’s life cycle breakoff using pesticides and biological control. In concern of the relatively severe of the impact caused by the use of synthetic pesticides, the application of natural ingredients, such as botanical pesticides, is a wise choice. It is a low-to-no severe effect to the environment and relatively safe for humans and animals. This study aimed to investigate the effectiveness of larvicide derived from plantain peel’s extract (Musa sapientum) against L3 larvae of Aedes sp. This study was a quantitative study, performing an experimental approach using a post-test control group design. An amount of 600 larvae were employed, then taken by using purposive sampling technique.The results were analyzed using SPSS for windows 21. The first test was the data normalization, obtained p>0.05 which means data were normally distributed, then was Pearson correlation test, obtained significant value 0.000 <0.05 which means the significant correlations, and the Pearson correlation coefficient of 0.987, very close to 1, which means a strong relationship between variables. The probit regression analysis then performed with the results of 0,516 for LC50 and 0,815 for LC90. Further study is needed to determine the active compound contained in the plantain peel’s extract (Musa sapientum) that plays the most as larvicides. Keywords: Effectiveness, plantain peel’s extract, larvae of Aedes sp.